The Level of Anxiety of Leprosy Patients in terms of Demographic Characteristics of Respondents - Sri Wahyuni; Christina Dewi Prasetyowati (Gaster, 2021)
Leprosy is a chronic contagious disease caused by the mycobacterium leprae bacteria which attacks the skin and peripheral nerves. This disease can cause physical disabilities if not treated properly. Physical disabilities that appear can cause psychological problems such as anxiety. The purpose of this study was to analyze the level of anxiety in patients with leprosy based on respondents' demographic characteristics. This type of research is analytic observational with a cross-sectional research design. The sample in this study were 106 leprosy patients, with the accidental sampling technique. Data collection using a questionnaire consisted of demographic characteristics, namely age, gender, occupational education, degree of disability, and the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis used the chi-square statistical test.Â  Results Age, employment, education, and patients' disability degree were associated with patient anxiety (p-value <0.05), while gender was not associated with patient anxiety (p-value> 0.05). Conclusion The variables of age, education, employment, and patients disability degree can affect anxiety in leprosy patients.